South African Economy - Brixen, Peter (Routledge Studies in Development Economics, 1996)
What are the macroeconomic prospects for South Africa until the new millennium? Two methods of macroeconomic modelling, associated with the World Bank and IMF, are used here to generate three scenarios, based on moderately optimistic projections. The methodology used can be applied to other developing countries.